Drug utilization pattern among type II diabetic patients in Palestine - Murad Abualhasan; Mai Awad; Waleed Sweileh (BMC Health Services Research)
Abstract Background Diabetes mellitus is a common metabolic disorder marked by hyperglycemia. Studying the use of anti-diabetic medications is essential for promoting proper drug use and improving healthcare planning. Objective This study aims to examine the drug utilization patterns and prescribing practices among Type 2 Diabetic Patients in Palestine. Specifically, it seeks to identify the most commonly prescribed medications, evaluate adherence to clinical guidelines, and assess factors influencing drug utilization at diabetes healthcare centers operated by the Ministry of Health (MOH) in Palestine. Methods A cross-sectional survey was conducted among 400 randomly selected patients with T2DM attending diabetic clinics in the northern and central regions of the West Bank, Palestine. Data on prescribing patterns and medication adherence were collected through patient interviews, and ethical guidelines were strictly followed throughout the study. Results The study found that metformin was the most frequently prescribed initial therapy for patients with T2DM. Medication adherence was notably high, with 68% of patients consistently taking their medications as directed, although 24% reported occasionally forgetting to do so. Approximately 90% of patients followed the prescribed dosage exactly as instructed. There were no statistically significant differences in metformin prescribing patterns across the regions; prescriptions for glimepiride varied significantly (p = 0.01). Combination therapies were also commonly used. Conclusion This research can enhance our understanding of diabetes treatment methods, patient adherence, and the factors influencing prescription decisions. Ultimately, this will support the development of more effective strategies for diabetes management.